Built Environment and HIV Linkage to Care in Rural South Africa - Nosipho Shangase; Brian Pence; Sheri A. Lippman; Mi-Suk Kang Dufour; Chodziwadziwa Whiteson Kabudula; F. Xavier Gomez-Olive; Kathleen Kahn; Audrey Pettifor (My University, 2023)
Background: We assessed built environment (residential density, landuse mix and aesthetics) and HIV linkage to care (LTC) among 1,681 (18–49 years-old) residents of 15 Mpumalanga villages, South Africa. Methods: Multilevel models (linear-binomial) were used for the association between built environment, measured using NEWS for Africa, and LTC from a clinical database of 9 facilities (2015–2018). Additionally, we assessed effect-measure modification by universal test-and-treat policy (UTT). Results: We observed, a significant association in the adjusted 3-month probability of LTC for residential density (risk difference (RD)%: 5.6, 95%CI: 1.2–10.1), however, no association for land-use mix (RD%: 2.4, 95%CI: 0.4, 5.2) and aesthetics (RD%: 1.2, 95% CI: 4.5–2.2). Among those diagnosed after UTT, residents of high land-use villages were more likely to link-to-care than those of low land-use villages at 12 months (RD%: 4.6, 95%CI: 1.1–8.1, p < 0.04), however, not at 3 months (RD%: 3.0, 95%CI: 2.1–8.0, p > 0.10). Conclusion: Findings suggest, better built environment conditions (adequate infrastructure, proximity to services etc.) help facilitate LTC. Moreover, UTT appears to have a protective effect on LTC.
Keywords: HIV linkage to care, Agincourt Health and Demographic Surveillance System, built environment, universal test and treat, South Africa